Humanities and Artificial Intelligence: Ethical Challenges, Creativity, and the Future of Humanity - Samsidar (Kamara Journal, 2026)
The rapid advancement of Artificial Intelligence (AI) has significantly transformed the humanities, reshaping how meaning, creativity, and cultural memory are produced and interpreted. Rather than merely replacing human roles, AI introduces complex ethical and epistemological challenges that redefine human–machine relations. This study aims to critically analyze the ethical implications and creative transformations resulting from AI integration in the humanities and to propose a human-centered conceptual framework for sustainable collaboration. The research employed a qualitative approach using systematic literature review and critical thematic analysis of peer-reviewed studies on AI ethics, digital humanities, and human–AI co-creation. The findings reveal three interconnected dimensions: technological disruption that reconfigures authorship and cultural production; ethical challenges involving bias, privacy, accountability, and human dignity; and creative co-creation models in which AI functions as an augmentative partner rather than a replacement. The discussion highlights that sustainable integration requires transparent, accountable, and culturally sensitive AI systems grounded in human-centered principles. In conclusion, the future of human–machine relations in the humanities depends on balancing technological innovation with ethical responsibility and the preservation of human agency and cultural sustainability.